Flower Automata Pattern-Based Discrimination of Fibromyalgia From Control Subjects Using Fusion of Sleep EEG and ECG Signals - Barua, Prabal Datta; Kobayashi, Makiko; Dogan, Sengul; Baygin, Mehmet; Tuncer, Turker; Paul, Jose Kunnel; Acharya, U. R. (Ieee-Inst Electrical Electronics Engineers Inc, 2025)
Electroencephalogram (EEG) and electrocardiogram (ECG) signals provide vital insights into brain and heart activity and are widely used in automated medical diagnostics. This study introduces a novel, multimodal fibromyalgia detection system developed by the fusion of EEG and ECG signals recorded during sleep stages 2 and 3. The novelty of the model is the use of dynamic and interpretable feature engineering framework comprising of two innovations: 1) Flower Automata Pattern (FAP) for self-organized pattern-based feature extraction, and 2) Attention-Driven Wavelet Transform and Absolute Maximum Pooling (ADWTAMP) method for signal decomposition and compression. Three feature selection strategies-Neighborhood Component Analysis (NCA), Chi2, and the intersection of NCA and Chi2 (NCA<^>Chi2) - are employed to generate robust feature vectors, which are classified using k-nearest neighbors (kNN) and support vector machine (SVM) under the leave-one-record-out cross-validation (LORO CV) scheme. The final decision is derived through an iterative voting and greedy fusion approach. The proposed model achieved classification accuracies of 99.36% and 98.37% for sleep stages 2 and 3, respectively. Key advantages of the model include its high accuracy, low computational requirements (CPU-only execution), and explainable architecture. To the best of our knowledge, this is the first multimodal automata-based classification framework designed for fibromyalgia detection.
Keywords: Feature extraction; Brain modeling; Electroencephalography; Sleep; Electrocardiography; Accuracy; Computational modeling; Biological system modeling; Automata; Support vector machines; Attention maximum pooling; automata-based dynamic patterns; EEG and ECG signal classification; fibromyalgia detection; flower automata pattern; intersection-based feature selection